2015
DOI: 10.1155/2015/342420
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Quality of Life in 87 Chinese Patients with Disorders of Sex Development

Abstract: Objective. In the process of care for disorders of sex development (DSD), clinical decisions should focus on the long-term quality of life (QOL). We sought to investigate the QOL of patients with DSD in China. Design. Case-control study was carried out. Patients. 90 patients of DSD participated in the study. Finally, 87 patients were analyzed including Turner's syndrome (23), Noonan syndrome (2), androgen insensitivity syndrome (22), testicular regression syndrome (2), congenital adrenal hyperplasia (16), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 37 publications
(31 reference statements)
2
21
1
Order By: Relevance
“…When compared to previous studies also using the SF‐36 in adults with CAH, the f‐CAH‐pa group in this study showed a better HRQoL (Table a) …”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…When compared to previous studies also using the SF‐36 in adults with CAH, the f‐CAH‐pa group in this study showed a better HRQoL (Table a) …”
Section: Discussioncontrasting
confidence: 50%
“…This might be due to the inhomogeneous group distribution, larger variation and non‐normal distribution of the data. Using a different questionnaire (WHOQOL‐BREF, WHOQOL), other studies described the same effect . Likewise, previous analysis of the German DSD network study of adolescents with DSD reared as girls showed higher HRQoL scores than girls of the reference group regarding physical well‐being.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Patients could achieve future fertility by implantation of embryos fertilized with donated oocyte; for patients without uterus (AIS, testis regression and 17 OHD), oestradiol monotherapy in doses of 2 mg daily is appropriate and fertility would not be considered. Psychological consulting would improve the quality of DSD life …”
Section: Discussionmentioning
confidence: 99%